Helminth control for small ruminants in Malaysia - Abdullah Sani, Rehana; Musbah, Adnan; Cheah, Tong Soon; Panchadcharam, Chandrawathani (Veterinary Association Malaysia, 2004)
This paper reviews gastrointestinal helminths present in small ruminants in Malaysia and their pathogenic effects, studies on resistance to anthelmintics and worm control options which include grazing management, anthelmintics, medicated feed blocks, medicinal plants, breeding and biological control.